2011
DOI: 10.1590/s0104-14282011005000055
|View full text |Cite
|
Sign up to set email alerts
|

Obtenção e caracterização de compósitos utilizando poliestireno como matriz e resíduos de fibras de algodão da indústria têxtil como reforço

Abstract: O objetivo deste trabalho é utilizar fibras de algodão como material de reforço em materiais compósitos poliméricos utilizando o poliestireno como matriz e o poli(estireno-co-anidrido maleico) como agente compatibilizante. Os compósitos foram desenvolvidos em uma extrusora dupla-rosca co-rotacional, precedidos de uma pré-mistura em extrusora mono-rosca e moldados por injeção. Os compósitos foram avaliados mediante ensaios mecânicos, térmicos, termo dinâmico-mecânico e de morfologia dos compósitos produzidos. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 18 publications
3
15
0
8
Order By: Relevance
“…Similar results were observed by Borsoi et al 19 in studies with cotton fibers. The effect of the coupling agent was not significant in this the initial evaluation.…”
Section: Resultssupporting
confidence: 91%
“…Similar results were observed by Borsoi et al 19 in studies with cotton fibers. The effect of the coupling agent was not significant in this the initial evaluation.…”
Section: Resultssupporting
confidence: 91%
“…In particular, the use of natural fibers, such as sisal, jute, curaua, ramie and cotton, in polymer composites has grown in recent years, due to material abundance, low cost and low density, and due to their renewable characteristics. These materials are also less abrasive to processing equipment compared to synthetic fibers, which becomes very important when equipment costs are high [1][2][3] . Major advantages of synthetic fibers over natural fibers include lower moisture absorption of the former and their better adhesion with the polymer matrix 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Cotton fibers are usually found as waste from the textile industry, being usually deposited in landfills and dumps. Although cotton does not have high mechanical properties compared to similar fibers, it can be combined to polymers to yield composites with some mechanical properties superior to that of a pure polymer 3 Borsoi et al 3 studied the incorporation of cotton fiber in thermoplastic matrix composites and obtained satisfactory mechanical results, including higher impact and flexural strength as well as increased flexural modulus. Hashmi et al, 6 studied cotton/unsaturated polyester composites and reported an improvement in structural integrity of the material under sliding wear conditions, a decreased specific wear rate and a higher coefficient of friction with the addition of the fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Compósitos com fibras naturais têm propriedades mecânicas superiores ao polímero puro [3][4][5] e que a capacidade de processamento dos compósitos reforçados com fibras vegetais está diretamente relacionada ao índice de fluidez da matriz e ao teor de fibras utilizado [6] . Dentre as fibras vegetais utilizadas como reforço em compósitos estão as fibras de curauá.…”
Section: Introductionunclassified